WEALTH INEQUALITY AND INSTITUTIONAL DEVELOPMENT: MACROECONOMETRIC EVIDENCE FROM A GLOBAL SAMPLE (The South East European Journal of Economics and Business, 2023)
This paper examines the empirical relationship between institutions, particularly financial institutions, and wealth inequality using a global panel data set for the period 2010–2016. We conduct a dynamic economet- ric analysis of these relationships based on the Credit Suisse and World Bank data. Our results reveal that control of corruption and government effectiveness do not have statistically significant effects on wealth inequality. However, the findings indicate an unfavourable effect of domestic credit on wealth inequality as measured by the Gini coefficient for wealth. The long-run effect of domestic credit is persistent and cumulates over time. We also find evidence of relationships between wealth inequality on one hand, and inflation rate, employment in agriculture and government expenditure on the other. The findings imply that policy makers need to re-examine the role and rules in the financial intermediation sector to address the issue of wealth inequality and equal opportunities.